(untitled) (Baghdad Science Journal, 2025)
The study included 200 samples were collected from children under two years included (50 samples from each of Cerebrospinal fluid, Blood, Stool and Urine) from, (Central Children Hospital and Children’s Protections Educational Hospital) The Iraqi Ministry of Health, the Department of Health Baghdad .the period from the first of 2015 September to the first of December 2015, Were obtained isolates bacterial subjected to the cultural, microscopic and biochemical examination and diagnosed to the species by using vitek2 system .The results showed there were contamination in 6.5% of clinical samples. The diagnosed colonies which gave pink color on the MacConkey agar, golden yellow color on the Trypton Soy agar and green color on the Birillent Enterobacter sakazakii agar and gave a probability of 99% in the vitek 2 and were identified as Cronobacter sakazakii. The identifcation revealed of thirteen isolates, (6) isolated from Cerebrospinal fluid samples and its contamination with percent 12%, (7) isolated from blood samples and its contamination with percent 14% and not isolated bacteria from stool and urine samples. Detection of zpx gene showed the presence of this gene in 13(100%)of isolates